2010
DOI: 10.1111/j.1468-0408.2009.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance Reporting by Malaysian Local Authorities: Identifying Stakeholder Needs

Abstract: The concept of public accountability promotes the need for a comprehensive set of performance‐related information to satisfy the information needs of a diverse stakeholder interest group. However, literature concerned with the scope of information to be disclosed, and in particular within the context of a developing country, is limited. This paper identifies the information set which stakeholders of Malaysian local authorities consider relevant in the monitoring and assessment of local authority performance. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 34 publications
3
37
0
2
Order By: Relevance
“…The key feature of disclosure for the NPo such as public sector, charities and NGos is to satisfy stakeholders' needs (Dhanani & Connolly, 2012;Hyndman, 1990;Tooley et al, 2010). Various stakeholders have an interest in information about governmental entities and NPo for accountability discharge.…”
Section: Content Of Information Disclosurementioning
confidence: 99%
“…The key feature of disclosure for the NPo such as public sector, charities and NGos is to satisfy stakeholders' needs (Dhanani & Connolly, 2012;Hyndman, 1990;Tooley et al, 2010). Various stakeholders have an interest in information about governmental entities and NPo for accountability discharge.…”
Section: Content Of Information Disclosurementioning
confidence: 99%
“…Similarly, three Malaysian studies also indicate the wholesale adoption of private-sector styles of performance measurement systems in the public sector (Chiu, 1997;Shafie, 1996;Tooley et al, 2010). All of these studies are mechanistic in nature and, more importantly, offer no critical reflections on whether MA changes contributed to better service delivery to the public, as intended.…”
Section: Npm and Private-sector Management Styles: A Welcome Change?mentioning
confidence: 99%
“…Within this group, the item showing the highest disclosure, namely customer satisfaction (ADI78) is much lower than Wei et al's (2008) study which scored 58 per cent. In addition, the score achieved for ADI78 may not be a favourable situation as a prior study by Tooley et al (2010) found that customer satisfaction was perceived by Malaysian local government stakeholders as a very important information.…”
Section: Performance Disclosure Category (4 Groups 20 Items)mentioning
confidence: 79%
“…The first two items are required by the TC4/2007 to be disclosed. The third item, on the other hand, was listed as among the top 20 performance items which were perceived to be very important by stakeholders in study by Tooley et al (2010) on Malaysian local government. Assuming that stakeholders' information requirements from the Malaysian public sector is similar across different types of entities, it may be said that the high disclosure of ADI89 has partly met the stakeholders' information requirement.…”
Section: Performance Disclosure Category (4 Groups 20 Items)mentioning
confidence: 99%